Diffuse Arterial Thrombosis as a First Manifestation of Occult Malignancy - Marija Vavlukis; Irina Kotlar; Emilija Chaparoska; Emilija Antova; Sasko Kedev (Case Reports in Medicine)
Aim. To raise the awareness of a hypercoagulability state as it is often associated with the different types of malignancies. Venous thromboembolism is a frequent complication in these patients, and usually it happens after the diagnosis of cancer is confirmed. However, hypercoagulability disorders presenting as the first symptoms or signs in the cancer patients have rarely been reported. Furthermore, arterial thrombosis is extremely rare even in cancer patients. Method. Review of the case characteristics and literature review. Results. We present a case of 39-year-old woman who was admitted to our hospital because of intermittent claudication in the right lower extremity. CT angiography revealed multiple thrombi in the arterial system starting from the left ventricle, followed by a thrombus in the distal part of the descending aorta, in the superior mesenteric artery, and in the right popliteal artery. Further investigation of this young patient with no risk factors for hypercoagulable state and no other comorbidities led to complete work-up including diagnostic evaluation for malignancy. The suspicion was confirmed after performing upper endoscopy with biopsy, which revealed malignant neoplasm of the stomach. Conclusion. Whenever a patient suffers hypercoagulability disorders, even arterial thrombosis, we should always consider the possibility of a cancer.